Design and test of an underwater platform - II - Yong, Wei Hong (2012)
This report records a creation of a new underwater vehicle model similar to a submarine. Unlike the submarine’s steering principles of using rudder, this underwater platform make use of synthetic jet actuators (SJAs) for the replacement of steering. The purpose of SJAs is to help enhance low speed maneuverability of the vehicle.